Transplanted Oligodendrocyte Progenitor Cells Survive in the Brain of a Rat Neonatal White Matter Injury Model but Less Mature in Comparison with the Normal Brain. (4th August 2020) - Ogawa, Shino; Hagiwara, Mutsumi; Misumi, Sachiyo; Tajiri, Naoki; Shimizu, Takeshi; Ishida, Akimasa; Suzumori, Nobuhiro; Sugiura-Ogasawara, Mayumi; Hida, Hideki
Preterm infants have a high risk of neonatal white matter injury (WMI) caused by hypoxia-ischemia. Cell-based therapies are promising strategies for neonatal WMI by providing trophic substances and replacing lost cells. Using a rat model of neonatal WMI in which oligodendrocyte progenitors (OPCs) are predominantly damaged, we investigated whether insulin-like growth factor 2 (IGF2) has trophic effects on OPCs in vitro and whether OPC transplantation has potential as a cell replacement therapy. Enhanced expression of Igf2 mRNA was first confirmed in the brain of P5 model rats by real-time polymerase chain reaction. Immunostaining for IGF2 and its receptor IGF2 R revealed that both proteins were co-expressed in OLIG2-positive and GFAP-positive cells in the corpus callosum (CC), indicating autocrine and paracrine effects of IGF2. To investigate the in vitro effect of IGF2 on OPCs, IGF2 (100 ng/ml) was added to the differentiation medium containing ciliary neurotrophic factor (10 ng/ml) and triiodothyronine (20 ng/ml), and IGF2 promoted the differentiation of OPCs into mature oligodendrocytes. We next transplanted rat-derived OPCs that express green fluorescent protein into the CC of neonatal WMI model rats without immunosuppression and investigated the survival of grafted cells for 8 weeks. Although many OPCs survived for at least 8 weeks, the number of mature oligodendrocytes was unexpectedly small in the CC of the model compared with that in the sham-operated control. These findings suggest that the mechanism in the brain that inhibits differentiation should be solved in cell replacement therapy for neonatal WMI as same as trophic support from IGF2.